Perception About Household Decision-Making Process on Obtaining Maternal Health Services Among the Employed Women of Dhaka City - Hossain, A H M Kishowar; Dana, Gaylan Peyari Tarannum (Social Science Review, 2023)
Reducing maternal morbidity and mortality and ensuring maternal and new-born health have been one of the central goals of healthcare system in Bangladesh. In that connection care during and after pregnancy, especially antenatal and delivery, is critical to monitor the status of pregnancy both for mother as well as for expected new-born baby. The role of women’s decision-making in reproductive health is crucial one. This study intends to understand the role of household decision-making in obtaining maternal health services- its patterns access and reasons by using qualitative methods. The approaches are employed to explain woman’s decision-making process to utilize the service facilities. The findings of the study illustrate that decision-making processes should be understood and recognized in a wider social environment and as a multifaceted process that is closely tangled with local belief systems and social relationships. Combined knowledge of social images, women’s requirements and expectations can play an important role in confirming broader and more effective coverage of maternal healthcare, health authorities and to those in charge of maternal care services. Social Science Review, Vol. 38(2), December 2021 Page 105-116